Gluten-Free Diets. Issue 6 (November 2015) - Morin, Karen H.
Abstract : Gluten-free diets are becoming a common practice in the United States and other countries. Our nutrition expert, Dr. Morin, explains what you need to know to answer questions from patients about gluten-free diets and suggests resources where you can get more information.